Towards a carbon compensation framework: integrating embodied carbon transfer and carbon sequestration service flows in urban agglomerations - Chen, Jing; Liu, Xiangmin; Yang, Shan; Wang, Xingjian (Frontiers in Environmental Science, 2025)
IntroductionUrban agglomerations, as regions of concentrated economic activity, exhibit both embodied carbon transfer (ECT) driven by interregional trade and carbon sequestration service flows (CSSF) caused by spatial mismatches in carbon sink supply and demand.Research GapTraditional carbon compensation mechanisms often adopt a single perspective, limiting their ability to reflect interregional carbon responsibility.MethodsUsing the Beijing-Tianjin-Hebei (BTH) urban agglomeration as a case study, this paper proposes a “Flow-Zoning-Compensation” framework that integrates ECT and CSSF. It identifies inter-administrative carbon flow paths, clarifies compensation subjects and benchmarks, and generates differentiated compensation schemes to establish a fairer horizontal carbon compensation mechanism.Results(1) Economically developed cities (e.g., Beijing, Shijiazhuang): transfer embodied carbon to industrial cities (e.g., Tianjin, Tangshan, Handan), while ecological function zones (e.g., Zhangjiakou, Chengde) not only receive embodied carbon but also provide sequestration services; (2) Based on total net transfers, the 13 cities in BTH are divided into six payers and seven recipients, with Shijiazhuang (2.861 billion CNY) and Chengde (2.860 billion CNY) as the main payer and recipient, respectively.DiscussionThis mechanism offers a more comprehensive reflection of carbon responsibility and provides policy implications for coordinated low-carbon development and national-level compensation design.